Manajemen Strategi Kepala Madrasah Dalam Meningkatan Mutu Pendidikan Di Madrasah Aliyah Negeri 3 Bireuen - Rizki Hidayat Rizki Hidayat (Madrasa : Jurnal Ilmu Pendidikan dan Teknologi, 2025)
This study examines the strategic management of the head of Madrasah in improving the quality of education at Madrasah Aliyah Negeri 3 Bireuen. Using a qualitative case study approach, data were collected through observation, documentation, and interviews, utilizing both primary and secondary sources.The findings reveal that the head of the madrasah's strategy encompasses five key aspects. First, internal consolidation, which involves formulating the institution's vision and mission and establishing collaborative teams to align school goals. Second, needs analysis, focusing on gathering information related to students, teaching methods, and teacher strategies to tailor more effective learning approaches. Third, human resource development, implemented through teacher training, selective recruitment, performance evaluation, and the creation of a supportive learning culture. Fourth, monitoring and evaluation, aimed at assessing educational outcomes and serving as a foundation for continuous improvement. Fifth, follow-up planning, which includes regular meetings with teaching staff to devise concrete steps in overcoming challenges and enhancing the quality of education.